Reputation Crisis Due to Influencer Controversy: Implications for Brand Marketing Communication Strategies in Indonesia - Annisa Febrina; Rahul Ardian; Irma Fatmawati (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Influencer marketing has become a dominant strategy for brands in Indonesia, offering wide reach and strong audience engagement. However, the growing reliance on influencers also exposes brands to significant reputation risks, particularly when influencers become involved in public controversies. This study examines the impact of influencer-related reputation crises on brand image and evaluates how brands respond through their marketing communication strategies. Using a qualitative approach supported by case analysis from recent controversy-driven incidents, the research identifies key patterns in consumer reactions, media amplification, and the effectiveness of various crisis response strategies. Findings show that delayed responses, inconsistent messaging, and failure to distance from problematic influencers can intensify public backlash. Conversely, proactive communication, transparent clarification, and strategic message reframing help restore brand credibility more effectively. This study contributes to a deeper understanding of crisis communication within the context of influencer marketing and provides practical recommendations for Indonesian brands to manage emerging risks in the digital ecosystem.